2013
DOI: 10.3747/co.20.1548
|View full text |Cite
|
Sign up to set email alerts
|

Fallopian Tube Removal: “stic-Ing” it to Ovarian Cancer: What Is the Utility of Prophylactic Tubal Removal?

Abstract: The exact percentage of ovarian tumours arising from the tube is unknown. Some estimates set the association at up to half of these tumours, but recent reports have estimated a much higher proportion. Przybycin et al. determined the frequency of stic in 114 non-uterine gynecologic cancers and determined that stic was confirmed in 59% of the high-grade serous tumours, with 92% of the lesions found in the fimbriated portion of the tube and the remaining 8% in the ampullary region 6 . Furthermore, these investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…Ovarian cancers that originate from malignant transformation of endometriosis appear to be part of type I ovarian cancers, which are typically of endometrioid or clear cell histology, with defects in ARID1A. These tumors are slower growing and more indolent compared to type II ovarian cancers (1721). This genetic difference may explain the tendency for early stage and confinement to the pelvis in cancers associated with endometriosis in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancers that originate from malignant transformation of endometriosis appear to be part of type I ovarian cancers, which are typically of endometrioid or clear cell histology, with defects in ARID1A. These tumors are slower growing and more indolent compared to type II ovarian cancers (1721). This genetic difference may explain the tendency for early stage and confinement to the pelvis in cancers associated with endometriosis in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, about 47,000 hysterectomies were performed in Canada. So, if the hypothesis is correct and if the numbers are accurate, then large numbers of women who do not otherwise "need" a hysterectomy will have to undergo bilateral salpingectomy to achieve a 40% This issue of Current Oncology contains four articles [1][2][3][4] on the subject of the role of bilateral salpingectomy in preventing high-grade serous ovarian carcinoma. To the uninitiated, that idea may seem counterintuitive.…”
Section: The Numbers Gamementioning
confidence: 99%
“…Herzog and Dinkelspiel have suggested that bilateral salphingectomy with ovarian retention (BSOR) as a new standard for ovarian cancer risk reduction and examination of the tubes should be extended to the general population also. Herzog and Dinkelspiel [2] They suggest that when the true incidence of these precursor lesions are known, effective screening and preventive strategies can be developed.…”
Section: Studied 228mentioning
confidence: 99%
“…It is important to know the true incidence of the precursor lesions so that optimal screening and preventive methods can be employed. Herzog and Dinkelspiel [2]. As on date there are no effective screening test to detect early precursor lesions in the tubal epithelium.…”
Section: Introductionmentioning
confidence: 99%